Non-communicating rudimentary horn of a unicornuate uterus: clinical spectrum and diagnostic challenges: a case series - Utkalika, Karubaki; Mohapatra, Diptimayee; Hui, Benudhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Pregnancy or hematometra in a non-communicating rudimentary horn of a unicornuate uterus is a rare and potentially life-threatening condition, often misdiagnosed due to its atypical presentation and resemblance to other pelvic pathologies. We report three cases highlighting the varied presentations and diagnostic challenges associated with rudimentary horn anomalies: a 28-year-old woman presented with persistent lower abdominal pain and bleeding following a failed medical termination of pregnancy. Imaging revealed a 12-week live gestation in a non-communicating rudimentary horn; a 36-year-old woman with chronic dysmenorrhea and a suspected subserosal fibroid was intraoperatively diagnosed with a rudimentary horn; and a 45-year-old perimenopausal woman with irregular menstrual cycle and an adnexal mass was found to have hematometra within a non-communicating rudimentary horn. Early diagnosis of rudimentary horn anomalies remains challenging. A high index of suspicion and appropriate imaging (MRI/3D ultrasound) are essential for accurate diagnosis and timely surgical intervention to prevent complications.